Psychology and the Market - Glaeser, Edward L (American Economic Review, 2004)
Prospect theory, loss aversion, mental accounts, hyperbolic discounting, cues, and the endowment effect can all be seen as examples of situationalism – the view that people isolate decisions and overweight immediate aspects of the situation relative to longer term concerns. But outside of the laboratory, emotionally-powerful situational factors – frames, social influence, mental accounts – are almost always endogenous and often the result of self-interested entrepreneurs. As such, laboratory work and, indeed, psychology more generally, gives us little guidance as to market outcomes. Economics provides a stronger basis for understanding the supply of emotionally-relevant situational variables. Paradoxically situationalism actually increases the relative importance of economics.